Development of PjBL teaching module based on Jombang's local wisdom for training science entrepreneurship skills - Rukmana , Rinaldiyanti; Susantini, Endang; Raharjo, Raharjo; Borhan, Mohamad Termizi (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2024)
Utilizing local wisdom in teaching and fostering life skills such as science entrepreneurship has become an urgent priority, especially in meeting the demands of Society 5.0. This study aims to develop a valid project-based learning (PjBL) teaching module, grounded in Jombang's local wisdom, to train high school students in science entrepreneurship skills. The type of research is development (R&D), and the development model used is ASSURE. The subject of the research is the teaching module developed for 10th-grade high school students on waste management. The research instruments used are interview sheets and validity sheets. The type of research data uses quantitative descriptive analysis, and the research data analysis techniques include qualitative data in the form of interview results regarding local wisdom in the sugarcane plantation area of Jombang, and quantitative data in the form of validity sheets filled out by expert validators and practitioners. The validation results of the teaching module developed by the researchers received an average score of 3.76, categorizing it as highly valid. The study demonstrates that the PjBL module on waste management is valid for training science entrepreneurship skills. These skills are cultivated by integrating biology content on waste management with a project involving the production of briquettes from sugarcane bagasse waste. This integration promotes environmental conservation through the zero-waste concept within a project-based learning framework.